2022
DOI: 10.3389/frmbi.2022.994464
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microbiome diversity and cytokine expression is influenced in a sex-dependent manner during aging

Abstract: The microbiome and immune system have a unique interplay, which influences homeostasis within the organism. Both the microbiome and immune system play important roles in health and diseases of the aged including development of cancer, autoimmune disorders, and susceptibility to infection. Various groups have demonstrated divergent changes in the gut microbiota during aging, yet the compounding factor of biological sex within the context of aging remains incompletely understood, and little is known about the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Evidence suggests that microbiota composition shows sex-related differences ( Elderman et al, 2018 ) that can also affect immunoresponses ( Markle et al, 2013 ; Fischinger et al, 2019 ), and gut microbiota alterations are prominent during the aging process ( Falony et al, 2016 ; DeJong et al, 2020 ). In fact, a recent study demonstrated that microbiome and cytokines profiles were influenced by aging in a sex-dependent manner ( Webster et al, 2022 ). Given the interrelation of sex, age, immunity, and gut microbial composition, it is conceivable that the aging female mice in our study exhibited an exacerbated glia response (ADC group) that could be more responsive to probiotic-induced changes in gut composition (ADP group).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that microbiota composition shows sex-related differences ( Elderman et al, 2018 ) that can also affect immunoresponses ( Markle et al, 2013 ; Fischinger et al, 2019 ), and gut microbiota alterations are prominent during the aging process ( Falony et al, 2016 ; DeJong et al, 2020 ). In fact, a recent study demonstrated that microbiome and cytokines profiles were influenced by aging in a sex-dependent manner ( Webster et al, 2022 ). Given the interrelation of sex, age, immunity, and gut microbial composition, it is conceivable that the aging female mice in our study exhibited an exacerbated glia response (ADC group) that could be more responsive to probiotic-induced changes in gut composition (ADP group).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the connection between the immune system and the fecal microbiota, multiple investigations have substantiated the impact of cytokines, for example, previous studies 19,20 suggest that the immune system actively controls and regulates the fecal microbiota. This regulation is in uenced by factors such as gender and speci c cytokines, with the strongest interactions observed in the intestine 21 . Therefore, in the present study, our hypothesis that β-mannanase supplementation could modify the abundance, diversity and composition of the fecal microbiome in lactating sows was con rmed, although this did not re ect changes in serum cytokine concentrations.…”
Section: Serum Cytokine Concentrationsmentioning
confidence: 99%
“…The gut microbiota has been shown to influence circulating levels of pro-inflammatory cytokines (Mizutani et al, 2022). A recent study by Webster et al (2022) showed that serum IL-1β and IL-6 levels were correlated with the presence of certain bacterial strains in the gut microbiome. Mechanistically, butyrate, one of the SCFAs produced by the gut microbiota, has been shown to inhibit the inflammatory response elicit by lipopolysaccharides, TNFα and interleukins via GRP41 and GRP43, both in endothelial cells (Li et al, 2018) and in chondrocytes (Pirozzi et al, 2018), suggesting that the gut microbiota could stimulate bone growth by reducing inflammation.…”
Section: Inflammatory Cytokines and Other Possible Mechanismsmentioning
confidence: 99%